2004
DOI: 10.1111/j.1365-3121.2004.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

From rifting to spreading in the eastern Gulf of Aden: a geophysical survey of a young oceanic basin from margin to margin

Abstract: A geophysical survey in the eastern Gulf of Aden, between the Alula–Fartak (52°E) and the Socotra (55°E) transform faults, was carried out during the Encens–Sheba cruise. The conjugate margins of the Gulf are steep, narrow and asymmetric. Asymmetry of the rifting process is highlighted by the conjugate margins (horst and graben in the north and deep basin in the south). Two transfer fault zones separate the margins into three segments, whereas the present‐day Sheba Ridge is divided into two segments by a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 38 publications
2
141
0
Order By: Relevance
“…In addition, some recent studies have proposed the occurrence of exhumed mantle between the rift basin and the first oceanic crust, based on observations of outcropping rocks in the Alpine basins and the results of DSDP boreholes in Iberia and " " Newfoundland (Beslier et al 1996;Withmarsch et al 2001). This possibility has also been suggested for the Gulf of Aden eastern margin (Leroy et al 2004;d'Acremont et al 2005;Leroy et al 2010b;Watremez et al 2010;Lucazeau et al 2010). However, the evidence for a wide belt of exhumed mantle below the Neogene sediments in the Red Sea, as proposed by some authors (Voggenreiter et al 1988;Bohannon 1989;Voggenreiter & Hotzl 1989) is scanty.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, some recent studies have proposed the occurrence of exhumed mantle between the rift basin and the first oceanic crust, based on observations of outcropping rocks in the Alpine basins and the results of DSDP boreholes in Iberia and " " Newfoundland (Beslier et al 1996;Withmarsch et al 2001). This possibility has also been suggested for the Gulf of Aden eastern margin (Leroy et al 2004;d'Acremont et al 2005;Leroy et al 2010b;Watremez et al 2010;Lucazeau et al 2010). However, the evidence for a wide belt of exhumed mantle below the Neogene sediments in the Red Sea, as proposed by some authors (Voggenreiter et al 1988;Bohannon 1989;Voggenreiter & Hotzl 1989) is scanty.…”
mentioning
confidence: 79%
“…Rift shoulder uplift and faulting are generally reported as being of lower Oligocene in age, whereas another phase of faulting is inferred to occur at the Oligo-Miocene boundary. Rift blocks are observed in seismic profiles offshore the northern Gulf of Aden (Leroy et al 2004;d'Acremont et al 2005;d'Acremont et al 2006;Autin et al 2010;Leroy et al 2010b), indicating that extensional tectonics affected the rifted crust until the Late Miocene (Leroy et al 2012). …”
Section: " "mentioning
confidence: 99%
See 1 more Smart Citation
“…After rifting and break-up of the African continental lithosphere in the Aden rift (Lepvrier et al, 2002;Fournier et al, 2004Bellahsen et al, 2006;Petit et al, 2007;Tiberi et al, 2007;Gunnell et al, 2007), the nascent Sheba Ridge, first recognized by Matthews et al (1967) and Laughton et al (1970), rapidly propagated westward (~200 km/Ma), as indicated by the age of the oldest magnetic anomaly identified in the Gulf of Aden at the longitude of 54°E (An 5D, 17-18 Ma; Leroy et al, 2004;d'Acremont et al, 2006) and 51°E (An 5C, 16 Ma;Sahota, 1990;Huchon and Khanbari, 2003). Accretion at the Sheba Ridge is presently oblique at a poorly constrained full rate of about 2.5 cm yr -1 in its easternmost end.…”
Section: Geodynamic Setting Of the Aoc Triple Junctionmentioning
confidence: 99%
“…Because the Gulf of Aden is an ideal place to investigate the continental break-up and interaction of plume activity with oceanic spreading ridge system, many marine geophysical studies have been conducted in this region (e.g., Manighetti et al, 1997;Dauteuil et al, 2001;Bosworth et al, 2005;d'Acremont et al, 2006Leroy et al, 2004Leroy et al, , 2010. Many of these studies reported a melt anomaly in the Gulf of Aden associated with the Afar mantle plume and its influence on the seafloor spreading process.…”
Section: Introductionmentioning
confidence: 99%